IMPLIKASI HUKUM BAGI NOTARIS YANG TIDAK MELEKATKAN SIDIK JARI PENGHADAP PADA MINUTA AKTA - HARYATI, HARYATI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Post the revised Law Notary Act No. 30 of 2004 to Act No. 2 of 2014, the provisions of Article 16 paragraph ( 1 ) letter c , the obligations attaching penghadap fingerprint on the deed minuta cause multiple interpretations among notary . The existence of such obligations affect the position of a deed made by the notary . It is the background and how the legal implications for notaries who do not attach fingerprints on minutapenghadapdeed ? This study uses normative legal research , which examines the research problems of the provisions of existing law regarding liability attaches penghadap fingerprints on minuta deed . The analysis used is descriptive and qualitative analysis , fundamental analysis studies that document obtained from secondary law . Method of data collection carried out by the method of research literature that refers to the reference of legislation and supporting documents . In Article 1 paragraph 8 of Law No. 2 of 2014 on the Amendment of Act No. 30 of 2014 concerning Notary , poured understanding minuta original deed is a deed that includes the signature of the penghadap , witnesses and a notary , which is stored as part of the notary protocol . In the minutes of the deed under the provisions of the Act no fingerprints term . In Article 16 paragraph ( 1 ) letter c , shall require the notary to make the minutes of the notarial deed , as it reads : \" In the run position , the notary shall attach a letter and documents and fingerprints penghadap the deed minuta \" .Base on under clause in above mentions that the inclusion of Article 16 paragraph ( 1 ) letter c in UUJN , the maker of the Act provides an additional obligation to the notary to embed fingerprint on each minutapenghadap notarial deed made by him . It is open to interpretation among practitioners notary . What lies behind the provisions of Article 16 paragraph ( 1 ) letter c , is to identify the presence of penghadap if one day the penghadap deny his signature on Minuta Deed . The notarial deed is a legal product notary will not be dropped derajadnya be deed under the hand , when the minutes of the notarial deed is not glued to the fingerprint . Notaries who do not carry out the mandate of the office of Notary Act violated Article 16 paragraph ( 1 ) letter c , will be sanctioned in stages , namely sanctions include written warnings , suspension , dismissal with respect , not with respect dismissal.